THE USE OF DIGITAL PLATFORMS IN FINANCING MANAGEMENT IN PRIMARY SCHOOLS - Sofiatuz Zuhro; Imam taufik; Imelda Dian Rahmawati; Hidayatulloh (International Journal of Economic Integration and Regional Competitiveness, 2024)
Digital transformation in the field of education has influenced the teaching and learning process as well as the administration and financial management of schools. Financial management at the elementary school level is crucial for determining the quality of education, requiring principles of fairness, efficiency, transparency, and accountability. This study aims to analyze the use of digital platforms in financial management of elementary schools, identify the benefits and challenges faced, and find solutions to overcome these obstacles. The research method used is Systematic Literature Review (SLR). The research findings show that the implementation of digital-based financial management in schools has been widely adopted, including the use of applications, virtual accounts, and e-commerce. The benefits obtained include increased efficiency, transparency, and accuracy in fund management. However, the challenges faced include limitations in technological infrastructure, lack of understanding and skills among educators, and data security issues. Additionally, internet network factors and uneven internet literacy in the community also pose challenges. Thus, this research provides insights and guidance for schools and other stakeholders to improve the effectiveness and efficiency of financial management in elementary schools through digital technology.